Use of ash filtrate as an alternative to chemical disinfectant and its antimicrobial efficacy (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aims to prepare the ash filtrate (AF) from household ashes using an in-house-designed handmade filtration system and to observe the antimicrobial efficacy and sanitizing effects. Materials and Methods: Household ashes from various plant sources were collected, and AF was prepared through a handmade filtration system after adding water. The pH of stock AF was measured, and 20%, 40%, 60%, and 80% AF solutions were prepared by adding distilled water in appropriate proportions to obtain a wide range of pH values. The antimicrobial efficacy of AF against Salmonella spp. in vitro, Newcastle disease virus (NDV), and low pathogenic avian influenza virus (LPAIV) H9 N2 in ovo were analyzed. Contaminated eggs were individually sprayed or dipped with AF to detect the bacterial load on the eggshell surface. Further experimental use of AF as an egg sanitizer in routine biosecurity operations in broiler sheds was also evaluated. Results: The prepared AF showed high alkalinity; pH varied from 10.7 to 8.20 and contained a higher amount of K, Na, and Cl. The alkaline AF and its dilution gradually inhibited Salmonella growth and showed gradual pH-dependent antibacterial efficacy. Similarly, AF and its dilution showed a gradual decrease in viral titer against the LPAIV (H9N2); however, antiviral activity against the velogenic strain of NDV was quite steady. Applying AF as an egg sanitizer also reduced the bacterial loads significantly on the eggshell surface compared to untreated eggs. Moreover, AF having pH 10.5 experimentally used in routine sanitization practices of a boiler shed resulted in low bird mortality (10/210), higher body weight gain, and a low feed conversion ratio compared to the untreated control flock. Conclusion: The higher alkalinity of the AF is responsible for the antimicrobial activity of commercial disinfectants. Consequently, we can use AF as a low-cost, effective, natural antimicrobial agent to replace chemical disinfectants.J. Adv. Vet. Anim. Res., 11(4): 1007–1016, December 2024http://doi.org/10.5455/javar.2024.k851